SURG-05. NAVIGATED INTRA-OPERATIVE 2-D ULTRASOUND VS STANDARD NEURONAVIGATION IN HIGH GRADE GLIOMA SURGERY. (5th November 2018) - Moiraghi, Alessandro; Prada, Francesco; Delaidelli, Alberto; Goga, Cristina; Guatta, Ramona; May, Adrien; Bartoli, Andrea; Saini, Marco; Waelchli, Thomas; Bijlenga, Philippe; Schaller, Karl; DiMeco, Francesco
Abstract: Maximizing extent of resection (EOR) and reducing residual tumor volume (RTV) while preserving neurological functions is the main goal in the surgical treatment of gliomas. Navigated Intra-operative ultrasound (N-ioUS) is a real-time imaging technique which, combining the advantages of ultrasound and conventional neuronavigation (NN), allows for overcoming the limitations of the latter. We evaluate the impact of real-time NN combining ioUS and pre-operative magnetic resonance imaging (MRI) on maximizing EOR in glioma surgery compared to standard NN. We retrospectively reviewed a series of 60 cases operated on for supratentorial gliomas, 31 operated under the guidance of N-ioUS and 29 resected with standard NN. Age, location of the tumor, pre- and post-operative Karnofsky Performance Status (KPS), EOR and, if any, post-operative complications were evaluated. Volumetric pre-operative and 48hours post-operative MRI was used to determine EOR. The rate of gross total resection (GTR) in NN group was 44.8% and EOR≤90% 10.3%, whereas in N-ioUS group a 61.2% GTR rate was obtained with a 6.4% rate of EOR≤90%. The rate of RTV> 1cc for GBMs was significantly lower for the N-ioUS group (p=0.01) compared to the NN. In 13/31 (42%) RTV was detected at the end of surgery with N-ioUS. In 8 of 13 cases (25.8% of the cohort) surgeons continued with the operation until complete resection. Specificity was greater in N-ioUS (42% vs 31%) and positive predictive value (73% vs 54%). At discharge the difference between pre and post-operative KPS was significantly higher for the N-ioUS (p=0.0008). Using N-ioUS-based real-time guidance in glioma surgery we obtained superior results in terms of both EOR and neurological outcome, in comparison to standard NN. N-ioUS has proven usefulness in detecting RTV> 1cc. In tumors located nearby eloquent areas the technique was successfully combined with cortical and subcortical mapping techniques.